Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Turk Arch Pediatrics 2021
DOI: 10.5152/turkarchpediatr.2021.21147
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of More Severe MEFV Gene Mutations in Childhood

Abstract: Aim: This study aimed to present the demographic, clinical, and laboratory features of children clinically diagnosed with familial Mediterranean fever (FMF) and to predict more severe mutations by evaluating those findings. Methods: We enrolled cases diagnosed with FMF with a defined variation in at least one allele. The medical charts of the patients were reviewed retrospectively. The patients were grouped as homozygous, compound heterozygous, and simple heterozygous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The other MEFV variants in the patient, E167D and F479L, are not as common as V726A. 10 These variants are found in exons 2 and 5, and fall into the pathological category, therefore leading to a more severe course of the disease. A study reported V726A to have a milder phenotype compared to the E167D-F479L mutation.…”
Section: Discussionmentioning
confidence: 96%
“…The other MEFV variants in the patient, E167D and F479L, are not as common as V726A. 10 These variants are found in exons 2 and 5, and fall into the pathological category, therefore leading to a more severe course of the disease. A study reported V726A to have a milder phenotype compared to the E167D-F479L mutation.…”
Section: Discussionmentioning
confidence: 96%
“… 1 Although it occurs worldwide, it is most frequent in the population of the Mediterranean region. 2 Familial Mediterranean fever’s prevalence varies from 1 : 500 to 1 : 1000 in endemic countries with the highest reported prevalence of 1/395 from the central Anatolia region. Considering disease prevalence and population size, Turkey has the highest number of FMF patients in the world followed by Israel and Armenia.…”
Section: Introductionmentioning
confidence: 99%